Progress on synthesis, functionalisation and applications of graphene nanoplatelets - Zamiri, G.; Bagheri, Samira; Shahnazar, S.; Hamid, Sharifah Bee Abd (Springer Verlag (Germany), 2016)
Carbon is the fifteenth most abundant element in Earth's crust, and the fourth most abundant element in the universe. Carbon nanostructures, or nanocarbons, i.e. the low-dimensional nanomaterials, are being extensively researched for the past two decades because of their unique structure and electronic properties, prompting a huge interest in its fundamental research and applications in molecular electronics, materials science, energy storage and conversion, bio-medicine, sensing, and bio-sensing. Graphene was recently touted as a wonder material, because of its high-mechanical strength, high-electron mobility, lightness, flexibility, single-atom thickness, and near-transparency. These properties make graphene a very promising material for composites, thin films, electromagnetic shielding, barrier films, and sensors. This review focuses on the latest progress on the preparation and functionalisation of graphene nanoplatelets, and discusses its potential applications, future prospects, and challenges in the context of theranostic applications.